Status and population dynamics of the Critically Endangered Valcheta frog Pleurodema somuncurense on the Patagonian Somuncura Plateau - Velasco, Melina Alicia (2019)
Amphibian populations are declining globally. In this scenario, detailed informationon their ecology is crucial to determine the status and extinction risk of their populations and,therefore, better plan conservation activities. The Valcheta frog Pleurodema somuncurense is aCritically Endangered species, which is endemic to the Valcheta Stream, Patagonia, Argentina.We assessed the status of this species at the metapopulation level, which we consider is a key stepin planning management activities. We conducted visual encounter surveys from 2013 to 2019 todetermine the distribution range of each local population of the Valcheta frog. During 2015, wealso applied a capture-recapture survey to estimate the density and apparent survival of 1 localpopulation. We used POPAN models for density estimation and the classic model of Cormack-Jolly-Seber to estimate apparent survival, using snout?vent length as a covariate. The meta -population of the Valcheta frog is composed of 9 isolated local populations: 7 extant and 2 extinct.The extant populations have population sizes ranging from 243 to 4516 individuals. The small sizeof the smaller local populations makes their long-term viability in isolation unlikely. We found apositive correlation between the apparent survival and the snout?vent length of individuals. Ourresults showed that management strategies should be aimed at ensuring the long-term survival ofthis species, with a focus on the recovery of extinct populations, the restoration of disturbedhabitats and the improvement of connectivity between local populations.